Case 3705: Mantis limbata Brullé, 1838 (currently Ameles limbata) (Mantodea, Mantidae, Amelinae): proposed conservation of the specific name. - Wieland, F; Goldberg, J; Schütte, K (Bulletin of Zoological Nomenclature, 2017)
The purpose of this application, under Article 23.9.5 of the Code, is to conserve the specific name Mantis limbata Brullé, 1838 (Insecta, Mantodea). It is a junior primary homonym of Mantis limbata Hahn, 1835(Insecta, Mantodea). Mantis limbata Brullé, 1838 is currently assigned to the genus Ameles Burmeister, 1838 (Mantidae, Amelinae), whereas Mantis limbata Hahn, 1835 is assigned to the genus Stagmomantis Saussure, 1869 (Mantidae, Stagmomantinae). Both names have not been considered to be conspecific after 1899. Therefore, we propose to suppress the replacement name Ameles canaria Koçak & Kemal, 2008, that has been suggested for the junior primary homonym, for the purposes of priority in order to avoid nomenclatural confusion within the subfamily Amelinae.
Keywords: Ameles; Ameles canaria; Ameles limbata; Amelinae; Canary Islands; Central America; Insecta; Mantidae; Mantis; Mantis limbata; Mantodea; Nomenclature; North America; Stagmomantinae; Stagmomantis; Stagmomantis limbata; taxonomy